Indication and Structures and Management of Transcatheter Aortic Valve Implantation: A Review of the Literature - Doebler, Klaus; Boukamp, Karin; Mayer, Ernst-Dietrich (The Thoracic and Cardiovascular Surgeon, 2012)
Background Transcatheter aortic valve implantation (TAVI) is a new treatment option for patients with severe symptomatic aortic stenosis. Despite a lack of scientific evidence for a benefit of the procedure compared with surgical valve replacement or repair as the current gold standard and pending questions about safety and long-term results, a continuous and remarkable increase of its application in Germany can be observed.Methods In a systematic research, publications suitable for the deduction of criteria for indication and structural and process standards were identified.Results No appropriate studies exist to define scientifically sound criteria for indication and structural and process standards for TAVI. Two randomized controlled trials give hints for potential patient selection criteria. However, several interdisciplinary position statements of the most relevant scientific societies in Europe and North America provide recommendations for indication criteria and minimum structural and process requirements. TAVI should be used only in patients with contraindications for open surgery or highest perioperative risk. Multidisciplinary heart teams comprising at least one cardiac surgeon and one cardiologist are mandatory for patient selection and performance of TAVI. Structural equipment to carry out immediate open heart surgery is mandatory. Most recommendations require performing TAVI only in hospitals with a cardiac surgery unit. Participation in a registry is recommended.Conclusion Currently, TAVI should be restricted to patients with severe symptomatic aortic valve stenosis and contraindications against open heart surgery or maximum perioperative risk. The surgical risk should be assessed by a multidisciplinary team. The procedure should be performed by interdisciplinary heart teams in hospitals with a cardiac surgery unit.
Keywords: transcatheter aortic valve implantation; TAVI; indication; structural and process requirements